IMPACT OF A PROPRIOCEPTIVE TRAINING ON THE FUNCTIONAL CAPACITY OF THE ELDERLY - Sérgio Garcia; Marisa Cunha; Eugénia Mendes; Leonel Preto; André Novo (Associação Portuguesa dos Enfermeiros de Reabilitação, 2019)
Introduction: Human aging implies a reduction in the functional capacity of the elderly, and physical exercise is fundamental to improve it. Objective: To evaluate the effects of a Rehabilitation Nursing program of self-training on functional capacity in a group of elderly people. Method: Quasi-experimental study with evaluation before and after intervention. The sample consisted of 24 elderly people distributed by the intervention group (12) and the control group (n=12). The intervention program included 24 sessions over 12 weeks of implementation. The unipodal balance test, the Tinetti index for balance and gait, and physical fitness by the Rikli & Jones test battery were used as measuring instruments. Results: In the intervention group there was a positive evolution in relation to all variables evaluated, with statistically significant differences in the two moments of evaluation. In the control group, there were no statistically significant changes. Conclusion: This program of proprioceptive training demonstrated gains in the functional capacity of the elderly.